Eventos adversos a medicamentos en pacientes hospitalizados: prevalencia, causas y factores de riesgo. - del Rocío Hernández-Morales, María; Ramírez-Sánchez, Jorge Manuel; Mancilla-Hernández, Eleazar; Lara-Dávalos, Norma; Nazarala-Sánchez, Samara; Aguirre-Barbosa, Margarita (Revista Alergia de Mexico)
Objective: To determine prevalence, causes and risk factors of ADE in hospitalized patients of a General Hospital. Methods: Observational and analytical case-control study, carried out in patients hospitalized for adverse drug events, treated at the Hospital General Dr. Eduardo Vázquez N, in Puebla, Mexico, between, June 2019 to June 2021. For the statistical analysis, percentages, frequencies, means, odds ratio, χ², and multiple binary logistic regression were used. Data were analyzed using the Statistical Package for the Social Sciences 23 program. Results: A total of 132 patients (66 cases and 66 controls) were registered. Of the group of cases, 26 patients treated for medication error and 40 with adverse drug reaction were reported. The prevalence of adverse drug events was 3.6%. The drugs and factors associated with the most reported adverse events were: antibiotics, anti-inflammatories; average age of 35 years (SD: 17.41); gender: 39.3% men, 60.7% women; services reported with the greatest attention: Emergencies and Surgery; frequent route of administration: intravenous (32.3%); main symptoms: skin; symptoms associated with adverse drug reactions: type A pruritus [OR: 8.5, p = 0.001(CI95%: 0.035-0.393)], type B pruritus [OR: 11, p = 0.001 (CI95%: 0.021-0.368)]; urticaria [OR: 19, p = 0.005(CI95%: 0.007-0.412)]. Risk factors associated with adverse events were: female gender [OR: 2.6, p = 0.05 (CI95%: 1.33-5.43)], history of allergy [OR: 3.4, p = 0.033 (CI95%: 1.04-8.40)] and prolonged hospital stay [OR: 5.4, p = 0.023 (CI95%: 3.82-6.74)]. Conclusions: The majority of ADEs were EM or ADR type A, both preventable reactions, so patient safety should be a priority when prescribing.